On Contested Shores : The Evolving Role of Amphibious Operations in the History of Warfare - Friedman, B. A. (Brett A.); Heck, Timothy, 1982- (Book collections on Project MUSE., 2020)
"The basis for On Contested Shores has been under construction since before the Commandant released the planning guidance. As career Marine officers, who spent very little time at sea, the editors have long been concerned that the Marine Corps was becoming too land-centric, heavily reflecting the characteristics of a second land army. This has been true since 1991, when the Marine Corps participated in a land campaign in Iraq, and especially since 2001, when it participated in three land campaigns: Afghanistan, Iraq, and Syria. To fight these battles, the Marine Corps became heavier, upgraded equipment, and generally focused on counterinsurgency tactics vice amphibious warfare. While the Marine Corps always steps up to fight alongside the U.S. Army, its purpose is naval campaigns fought alongside the U.S. Navy. This book is in part a way to help figure out how to regain and maintain the skills necessary for maritime operations"--